Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2337/dc14-2585
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy and Nerve Dysfunction in Individuals at High Risk for Type 2 Diabetes: The PROMISE Cohort

Abstract: OBJECTIVEEmerging evidence suggests that peripheral neuropathy begins in the early stages of diabetes pathogenesis. Our objective was to describe the prevalence of peripheral neuropathy and nerve dysfunction according to glucose tolerance and metabolic syndrome status and examine how these conditions are associated with neurological changes in individuals at risk for type 2 diabetes. RESEARCH DESIGN AND METHODSWe studied 467 individuals in the longitudinal PROMISE (Prospective Metabolism and Islet Cell Evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
78
3
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(97 citation statements)
references
References 31 publications
(31 reference statements)
4
78
3
6
Order By: Relevance
“…We found that the prevalence of peripheral neuropathy was higher in those with prediabetes than those with normoglycemia, but the association was not significant in multivariable models. With many previous studies supporting,16, 32, 33 and some not supporting,23, 34 an association of prediabetes with peripheral neuropathy, our results do not push the overall level of evidence much in either direction. Our study is now the third to show an increased OR in those with prediabetes that does not meet statistical significance 22, 31.…”
Section: Discussioncontrasting
confidence: 96%
“…We found that the prevalence of peripheral neuropathy was higher in those with prediabetes than those with normoglycemia, but the association was not significant in multivariable models. With many previous studies supporting,16, 32, 33 and some not supporting,23, 34 an association of prediabetes with peripheral neuropathy, our results do not push the overall level of evidence much in either direction. Our study is now the third to show an increased OR in those with prediabetes that does not meet statistical significance 22, 31.…”
Section: Discussioncontrasting
confidence: 96%
“…Even if it dates back to 1994, MNSI clinical score is still considered valid: it was recently used to measure neuropathy in high-risk nondiabetic, prediabetic and new-onset diagnosed patients, showing a surprisingly high prevalence of neuropathy in these cohorts (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the application of a quantitative tool (the biothesiometer) could make the method more objective, even if the chosen cutoff is not necessarily shareable. No standardized VPT cutoff value to define the presence of peripheral neuropathy has been published to date (Lee et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous validation studies established a maximum score of 8 for the MNSI (15); however, they did not include the 10-g monofilament test. Here, we established a maximum possible score of 10, in accordance with recent epidemiological studies (8,16). In this analysis, the presence of DSPN was defined by a score greater than 2 (> 2) in the clinical examination component of MNSI (8).…”
Section: Physical Examination and General Testsmentioning
confidence: 99%
“…One of this is the Michigan Neuropathy Screening Instrument (MNSI), which consists of a self-administered questionnaire and a 5-item physical examination. This tool has been widely validated (6,7) and used to determine the presence of peripheral diabetic neuropathy in various longitudinal studies (8).…”
Section: Introductionmentioning
confidence: 99%